Green Central Banking, Climate Risk, and Price Stability Mandates: Institutional Conditions and Governance Safeguards - Nurbaidah, Siti Umi; Hidayah, Nur (Institut Bisnis dan Informatika Kesatuan, 2026)
This research is motivated by the increasing relevance of climate risk in macroeconomic dynamics, particularly for inflation and monetary policy transmission, which challenges the traditional boundaries of central bank mandates. The study aims to analyze the conditions under which climate-sensitive monetary instruments can be considered consistent with price stability, how the institutional context shapes their legal framing, and the governance safeguards necessary to prevent fiscal dominance. The method used is a qualitative approach based on policy discourse analysis, utilizing 45 official documents from the European Central Bank, Bank Indonesia, and the Network for Greening the Financial System for the period 2024–2026. The results show a significant increase in the integration of climate risk into the discourse on financial and price stability, despite the absence of formal changes in mandates. The findings also indicate that legal legitimacy depends on a measurable link between climate risk and monetary objectives and a governance design that maintains independence. This research emphasizes the importance of a risk-based approach and transparency in the design of monetary instruments. It is concluded that climate risk integration can be legitimately undertaken as a reinterpretation of the mandate, as long as it is supported by a disciplined and accountable institutional framework.